The power of an effective apology in the process of forgiveness and reconciliation in social media (2022)
An effective apology could have long lasting effects in social groups allowing the transformation of feelings and attitudes related to resentment, anger and guilt, at the same time that facilitates the reconstruction of cooperative and friendly relations. Therefore, in this document I will analyze the impact of an effective apology in the forgiveness process in social media. We developed a corpus linguistic analysis and a behavioural and physiological experiment to understand the relationship between an effective apology and forgiveness characteristics